COVID‐19's impact on type 1 diabetes management: A mixed‐methods study exploring the Peruvian experience. (5th July 2022) - Zafra‐Tanaka, Jessica Hanae; Najarro, Lizzete; Tenorio‐Mucha, Janeth; Lazo‐Porras, Maria; Bartra, Diego; Bazán, Gina; Berghusen Anteparra, María Claudia; Bonilla, Ursula; Motta, Vicky; Beran, David
Abstract: Introduction: The COVID‐19 pandemic has negatively impacted health services, especially in low‐and‐middle‐income countries, where care for chronic conditions such as diabetes was disrupted. Our study aims to describe the challenges faced by people living with Type 1 diabetes mellitus (T1DM) to access care during the COVID‐19 pandemic in Peru. Methods: A sequential explanatory mixed‐method study was conducted between May and September 2020 including health professionals involved in T1DM care, people with T1DM and their caregivers. The study consisted of a quantitative strand to gather general information through electronic surveys and a qualitative strand that involved in‐depth interviews. Results: For the quantitative study, we included 105 people with T1DM, 50 caregivers and 76 health professionals. The qualitative study included a total of 31 interviews; 16 people with T1DM, 14 health care professionals, and one representative from the Peruvian Ministry of Health (MoH). People with T1DM faced difficulties accessing consultations, insulin, monitoring devices and laboratory testing during the pandemic. Different phases of the Peruvian health system response were found. Firstly, an initial informal response to addressing T1DM care during the pandemic characterised by local initiatives to ensure continuity of care for people with T1DM. Following from this, a formal response was implemented by the MoH which focussed on reinforcing the primary level of care. Measures included teleconsultations and delivery of medicines, although these were not implemented in all health care establishments. Throughout the pandemic patient associations played an important role in organising and helping to counteract the impact of COVID‐19 on people with T1DM. Conclusions: The Peruvian health care system slowly adapted to the COVID‐19 pandemic to provide care for people with T1DM. However, people with T1DM had difficulties to access care. Thus, reinforcement of interventions such as communication between levels of care, teleconsultations and delivery of medicines was urgently needed. Patient associations' capacity to respond should be considered by local authorities and civil society should be part of the health system response. Highlights: In Peru, non‐communicable diseases (NCD) care was initially neglected during the pandemic given the scarcity of resources. People with Type 1 diabetes mellitus (T1DM) had limited access to consultations and insulin. Civil society organised and mitigated the impact of COVID‐19 on health care access. Civil society should be involved by local authorities when planning for public health interventions.